Obowiązki i prawa rodziny w świetle posoborowych dokumentów kościelnych - Dyduch, Jan (Prawo Kanoniczne, 1994)
The Catholic Church observes the year 1994 as International Year of the Family in accordance to the announcement made by the United Nations. For this reason it is proper to talk over the obligations and the rights which a family exercises in a secular society and in the Curch. These rights and obligations are contained and treated in the following postconciliar documents of the Church: 1. The Encyclical Humanae Vitae, 1968; 2. The Adhortation Familiaris Consortio, 1981; 3. The Codex of Canon Law, 1983; 4. The Charter of the Family Right, 1983; 5. The Adhortation Christifideles Laici, 1988. Propagating of the family rights and obligations is necessary in view of the situation of the contemporary family, encountered by a multiple crisis. Calling in question of the sense of the family, the mentality adverse to life, and divorces are the most severe indications of that crisis. The basic right and obligation of a family is its service to the life itself, expressed in the procreating and upbringing of children. Doing this, a family needs protection and support from a civil authority which ought to maintain the appropriate policy favourable for the family and its development. A Christian family, sacramentally incorporated into the organism of the Universal Church, constitutes a „Home Church” and participates in Christ’s triple mission: prophetic-evangelizing, priestly-santifying and royal-apostolic. The family is a subject of the Church’s constant pastoral care.